The Differentiation of CD4+ T-Helper Cell Subsets in the Context of Helminth Parasite Infection - Bouchery, Tiffany; Kyle, Ryan; Ronchese, Franca; Le Gros, Graham (Frontiers in Immunology, 2014)
Helminths are credited with being the major selective force driving the evolution of the so called “type 2” immune responses in vertebrate animals, with their size and infection strategies presenting unique challenges to the immune system. Originally, type 2 immune responses were defined by the presence and activities of the CD4+ T helper 2 subset producing the canonical cytokines IL-4, IL-5 and IL-13. This picture is now being challenged by the discovery of a more complex pattern of CD4+ T helper cell subsets that appear during infection, including Tregs, Th17, Tfh and more recently Th22, Th9, and ThGM. In addition, a clearer view of the mechanisms by which helminths and their products selectively prime the CD4+ T cell subsets is emerging. In this review, we have focused on recent new data concerning the selective priming, differentiation and functional role of CD4+ T helper cell subsets in the context of helminth infection. We argue for a re-evaluation of the original Th2 paradigm and discuss how the observed plasticity of the T helper subsets may enable the parasitized host to achieve an appropriate compromise between elimination, tissue repair, containment and pathology.